2003
DOI: 10.1590/s0100-879x2003000800017
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of integrin subunits on adherent and nonadherent mast cells

Abstract: Mast cell progenitors arise in bone marrow and then migrate to peripheral tissues where they mature. It is presumed that integrin receptors are involved in their migration and homing. In the present study, the expression of various integrin subunits was investigated in three systems of adherent and nonadherent mast cells. Mesentery mast cells, freshly isolated bone marrow-derived mast cells (BMMC) and RBL-2H3 cells grown attached to tissue culture flasks are all adherent mast cells and peritoneal mast cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A previous investigation from our laboratory has shown that while mast cells freshly isolated from rat bone marrow express the integrin subunits α4, α5, α6, β1 and β7 on their surface, the more mature, adherent mast cells expressed significantly more α4 integrin [41]. This change in expression of α4 integrin may be related to the release of MCp from the bone marrow to populate peripheral sites.…”
Section: Discussionmentioning
confidence: 94%
“…A previous investigation from our laboratory has shown that while mast cells freshly isolated from rat bone marrow express the integrin subunits α4, α5, α6, β1 and β7 on their surface, the more mature, adherent mast cells expressed significantly more α4 integrin [41]. This change in expression of α4 integrin may be related to the release of MCp from the bone marrow to populate peripheral sites.…”
Section: Discussionmentioning
confidence: 94%
“…Although a typical consequence of compromised cell-ECM interactions is cell death, RBL cells have been shown to be viable in non-adherent conditions (Grodzki et al, 2003). This is a result that is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Their major role in disease was originally described as the major effector cell in the pathogenesis of allergic reactions (2). Mast cells derive from committed bone marrow precursors that migrate to peripheral tissues, where they fully mature into phenotypically distinct mast cells (3). Two phenotypically distinct mast cell populations have been described in humans on the basis of their neutral protease composition: The MC T (containing tryptase) and the MC TC (containing tryptase and chymase).…”
mentioning
confidence: 99%